ANALISIS EFEKTIVITAS STRATEGI PEMBELAJARAN BERBASIS PROYEK DALAM MENINGKATKAN MOTIVASI DAN HASIL BELAJAR MAHASISWA TEKNIK BANGUNAN - Tiara Riyanti (ADIBA : JOURNAL OF EDUCATION, 2024)
The Project-Based Learning (PjBL) model has become popular across various educational levels, including construction engineering education. The aim of this research is to analyze the effectiveness of the PjBL strategy in enhancing motivation and learning outcomes among Construction Engineering students. The research method employed is literature analysis, involving the review and synthesis of various empirical and theoretical studies. The analysis results indicate that PjBL significantly enhances students' motivation to learn and encourages active participation in projects related to real-world applications. The findings of this research suggest that PjBL can be an effective learning strategy to improve motivation and learning outcomes for Construction Engineering students. Additionally, the study recommends educational practitioners to consider PjBL as a primary teaching method and proposes further research in this field.